(untitled) (Asian-Australasian Journal of Bioscience and Biotechnology, 2016)
Begging is one of the major social problems. There are some certain changes as the result of urbanization. The people used to beg as they are losing the social security’s following the breaking up of the joint family. The begging has expanded all around in Bangladesh. The beggars are in bus, markets, roads, houses in different places. General objective of the study was to know the situation of the old aged people engaged in bagging in Dhaka city. Specific objectives were to know the family background of the aged-beggars, to understand the socio-economic factors those are responsible for old age begging and to know the quality of life/ life style of old age street beggars. It was a qualitative study has used to explore causation in order to find situation of the old age beggars and their condition, situation as well. After analyzing the cases, it is seen that the majority are in begging because of they are not having assets and income securities. The male cases are widower, females are widow or abandoned. Some issues are also serious including the medical, food and habitat which are very important indeed. Every older person wants to be active in later life. By which he or she takes a part of development for the country and nation everyone should be aware to fulfill their daily needs. We should take some necessary steps in individuals, family, society, country as well globally for the well being of elderly street beggar in various places. Asian Australas. J. Biosci. Biotechnol. 2016, 1 (2), 346-352